Evaluation of Gram Stain Error Rates of Clinical Specimens - Sajjad, Rabia; Zaman, Gohar; Mirza, Irfan Ali; Hussain, Wajid; Khurshid, Umar; Shehzad, Asim (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine important errors in initial Gram staining of clinical specimens and evaluate the types of Gram-stain errors.Study Design: Cross-sectional study.Place and Duration of Study: Microbiology Department, Armed Forces Institute of Pathology, Rawalpindi Pakistan, from Aug 2018 to Feb 2019.Methodology: Gram staining and culture inoculation of all specimens were performed per recommended guidelines. The Gram stain results on day-0 were compared with the results of the culture on day-2. There was no discrepancy if similar organisms were obtained on culture as on Gram stain. Nevertheless, if the Gram stain and culture results were not similar, it was termed a discrepancy. The consultant microbiologist reviewed all discrepant slides, and if not resolved, possible causes of error were sought, and the results documented.Results: Of the total 300 clinical specimens, errors were observed in the initial gram staining of 29 specimens (9.7%), whereas 271(90.3%) specimens were error-free. Upon evaluating these 29 errors, 11(38.0%) were observer errors which were resolved when reviewed by a consultant microbiologist. 14(48.0%) were technical errors, and 4(14.0%) results were discrepant due to the presence of anaerobic organisms, missed on initial aerobic cultures.Conclusion: The frequency of Gram stain errors in our study (9.7%) is not very high; nevertheless, it can have severe consequences in critical samples from seriously ill patients if wrong empirical antimicrobial treatment is begun based on a wrong initial Gram stain result.